Do coping with stress and organizational justice influence the dimensions of learning organization among the executive in public and private peninsular Malaysia / Noor Nadia Raub - Raub, Noor Nadia (Faculty of Business and Management, 2010)
Interest in learning organization has steadily increased over the past decade. This research was conducted to see the reliability among the independent variables and dependent variables. The research was conducted in the companies in Public and Private Peninsular Malaysia. The study explores the relationship between the dimension of Learning Organization and the two sub independent variables, which are coping with stress and organizational justice. They are 14 specific research hypotheses which have to be answered in this research whether, it has a relationship or not. It can be known by reading this research paper. The independent variables are the dimension of organizational justice and coping with stress. While the dependent variables was the dimension of learning organization. There are seven dimension of learning organization, as defined by Marsick and Watskins (2003). There are: (a) continuous learning; (b) inquiry and dialogue; (c) team learning; (d) provide leadership; (e) empowerment; (f) system connection and (g) embedded system. In this research paper also has a research methodology where in that chapter there are research design, data collection method, sampling, questionnaire design and the most important is pilot test. This is because before the researcher done a research, they must do the pilot test first, to see if it is effective or not the topic that they want to do the research. The finding part is the evidence part whether the research is significant or has a relationship or not. In this part, we can conclude the research.